Enhancing agricultural resilience through Pre-Season and In-Season Advisories - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
AICCRA project provides pre-season and in-season advisories to farmers in the drylands through the Intelligent Systems Advisory Tool (iSAT). Leveraging historical climate trends and current/future weather conditions, iSAT develops weather advisories delivered via short message service (SMS) directly to farmers' mobile phones. This innovative approach empowers farmers with timely information, covering land preparation, crop selection, planting, weeding, and real-time pest and disease control and management updates. Implemented during the MAM 2023 long rains and OND 2023 ‘Short rains’ in Kitui, Makueni and Taita Taveta Counties, this technology delivers specific and timely advisories supporting farmers' decision-making amidst climate change and variability.